IMPLEMENTASI JUAL BELI MURABAHAH PADA PEMBIAYAAN BANK SYARIAH - M. Aditya Ananda, MA (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2019)
The implementation of Murabahah concept on syaria bank financing has differences with the concept of murabahah in Fiqh. This happens to adapt or adapt to the functioning of the bank as the intermediary party rather than as the seller who already has the goods available. Therefore, Murabahah on syaria banking is called Murabahah KPP (Murabahah to purchase buyer) or bay'ul muraabahah lil amir bisy-Syiraa'. The name is more appropriate if in the context of the bank as the party selling by first buying goods from the supplier by the bank itself. For the purchase of goods represented by the customer, the financing is called Murabahah. This naming is not a standard thing, but to identify the transformation of the development of Murabahah concept on syaria bank financing.